Postoperative Kyphosis in Cervical Spondylotic Myelopathy: Cut-off Preoperative Angle for Predicting the Postlaminoplasty Kyphosis. Issue 10 (15th May 2020) - Machino, Masaaki; Ando, Kei; Kobayashi, Kazuyoshi; Morozumi, Masayoshi; Tanaka, Satoshi; Kanbara, Shunsuke; Ito, Sadayuki; Inoue, Taro; Ito, Keigo; Kato, Fumihiko; Ishiguro, Naoki; Imagama, Shiro
Abstract : Study Design: A prospective cohort study. Objective: This study aimed to investigate the relationship between preoperative cervical sagittal alignment and postoperative kyphosis in patients with cervical spondylotic myelopathy (CSM) and to determine the cut-off angle for predicting the postlaminoplasty kyphosis. Summary of Background Data: There have been several reports describing a cervical kyphosis after laminoplasty. However, there has been no study on the cut-off angle for predicting the postoperative kyphosis in a large series of patients with CSM. Methods: A total of 1025 consecutive patients with CSM (642 men and 383 women; mean age, 64.4 yr; range, 23–93 yrs) who underwent laminoplasty were included. The average follow-up period was 30.0 months. Radiography was performed before the surgery and at final follow-up. The cervical alignment with neutral view was measured by using the Cobb method. An alignment of C2–7 lordotic angle more than 0° was defined as lordosis and C2–7 lordotic angle less than 0° was defined as kyphosis. The incidence of postoperative kyphosis was evaluated on lateral radiographs. Results: In all patients, the mean C2–7 alignment in the neutral position was 11.5° lordotic before surgery and 14.2° lordotic at final follow-up. In the patient without preoperative kyphotic alignment, receiver operating characteristic curve of preoperative C2–7 lordotic angle showed 7° as a predictor for the postlaminoplasty kyphosis (area under the curve  = 0.75, P  < 0.0001). Among the preoperatively 720 patients with lordosis more than 7°, postoperative kyphosis was observed in 20 patients (2.8%), whereas in the preoperatively 191 patients with lordosis less than 7°, postoperative kyphosis was seen in 28 patients (14.7%). Conclusion: The cut-off value of preoperative C2–7 lordotic angle for predicting the postlaminoplasty kyphosis was 7° in CSM patient without preoperative kyphotic alignment. Level of Evidence: 3 Abstract : This study aimed to investigate the relationship between preoperative C2–7 lordotic angle and postoperative kyphosis in patients with cervical spondylotic myelopathy (CSM). The cut-off value angle predicting the postlaminoplasty kyphosis was 7° in the patient without preoperative kyphotic alignment.